Building Trauma Informed Teachers: A Constructivist Grounded Theory Study of Remote Primary School Teachers’ Experiences With Children Living With the Effects of Complex Childhood Trauma - Brown, Meegan; Howard, Judith; Walsh, Kerryann (Frontiers in Education, 2022)
The experiences of remote teachers who work with children living with the effects of complex childhood trauma is under explored. Children from remote areas of Australia are vulnerable to complex childhood trauma as their communities can face the effects of colonization, higher rates of disadvantage and exposure to potentially traumatic circumstances, such as natural disasters and family and community violence. This is compounded by the tyranny of distance in accessing effective supports. In such contexts, the roles of schools and teachers in addressing the debilitating impacts of trauma are both vital and amplified. This article summarizes a qualitative study, incorporating constructivist grounded theory, that generated a new theory to explain social processes that teachers in remote schools undergo when working with the effects of complex childhood trauma. Data were collected from teachers in individual interviews (n = 23) and a focus group. Data were analyzed using constant comparative method, emergent themes were categorized, leading to the development of the grounded theory, Building Trauma Informed Teachers. This overarching theory consists of seven categories. This study contributes insights into the scope and nature of the work of teachers in remote schools and recommends ways in which cognate systems can prepare and support teachers for their professional work supporting and educating trauma-impacted children.